A Study on the Sandwich-Style Notched Tensile Specimens for Different Materials through a Simulation Analysis - Lee, Jung-Ho; Cho, ae-Ung (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study designed a model that used the sandwich-style notched tensile specimens of the same specifications by applying to the properties of CFRP, stainless steel, and aluminum, and performed a test simulation.Methods/Statistical analysis: The study used CATIA design software to perform the 3D modeling of the sandwich-style notched tensile specimens with the properties of CFRP, a composite material, and stainless steel and aluminum, both ordinary metals, and then, performed a tensile test simulation.Findings: By designing the sandwich-style notched tensile specimens of the same specifications and performing a test simulation, we were able to verify the tensile strength and durability of the specimens for the different materials. This study result showed that unlike the specimens for the ordinary metals, those specimens with the properties of the composite material of CFRP first showed maximum load instead of breaking immediately due to the fibers in CFRP, before they resisted displacement in response to the alternately increasing and decreasing load until it fractured. To be specific, we saw that the CFRP specimens had the more excellent tensile strength and durability.Improvements/Applications: The data obtained from the studies will serve as the basic data for studies on the composite materials like CFRP and other various materials.Â Â Â